(untitled) (Bangladesh Medical Journal, 2014)
A cross sectional study was carried out in the department of Obstetrics and Gynae of Dhaka Medical College Hospital (DMCH). Two hundred thirty two cases who fulfilled the inclusion criteria were studied. This study aimed to assess the outcome of implementation of WHO modified partograph in labour management with special interest to evaluate the fetomaternal outcome. Among the 232 cases, engaged fetal head had more vaginal delivery, 78.8% than unengaged head. The rate of caesarean section was 26.9% in women with unengaged head vs 11.5% in women with engaged head in this study. This study showed that there was no LUCS when cases remained within alert line and outside the action line in partograph all were delivered by caesarean section. The rate of spontaneous delivery was more 58.6% who did not require any augmentation. On the other hand 80 percent cases of LUCS needed augmentation. In this study, 84.1 percent babies cried spontaneously, 12.9 percent cried after resuscitation and only 3 percent needed admission to neonatal care unit. The frequency of neonatal resuscitation was higher for the group who crossed the alert line (27.8%) or action line (23.1%), than the group which remained within alert line (8.6%) in partograph. Thus with proper monitoring and maintenance of partograph in labour prolonged labour or obstructed labour and their sequelae can be avoided, operative interventions will be reduced and thus fetomaternal outcome will be improved. DOI: http://dx.doi.org/10.3329/bmj.v41i1.18781 Bangladesh Medical Journal 2012 Vol. 41 No. 1; 42-44